Evolução de pacientes cirróticos pelo vírus da Hepatite C submetidos a transplante renal - Emori, Christini Takemi [UNIFESP] (2019)
Background: The prevalence and clinical epidemiological profile of hepatitis C virus (HCV) infection has changed over time and the renal transplant (RTx) in cirrhotic patients is still a challenge. Aim: To verify changes in renal transplant recipients comparing two different decades and to analyze evolution of cirrhotic patients after the RTx. Material and methods: RTx with HCV referred to renal transplant from 1993 to 2003 (A) and from 2004 to 2014 (B) were retrospectively studied. Demographic and clinical characteristics and outcomes of decompensation, loss of graft and hepatic cause of death were compared between groups A and B as well as between cirrhotic (C) and non-cirrhotic (NC) patients. Results: Among 11,715 RTx, the prevalence of HCV was 7%in A and 4,9%in B. In the more recent period (B) mean age was higher (46.2 vs 39.5 years), with more males(72% vs 60.7%), larger number of deceased donors (74% vs 55%), higher percentage of previous renal transplant (27% vs 13.7%), less frequent history of blood transfusion (81% vs 89.4%), lower prevalence of HBV co-infection(4.7% vs 21.4%) and higher percentage of cirrhotic patients (13% vs 5%). Patients of group B more frequently underwent HCV treatment (29% vs 9%), less frequently used azathioprine (38.6% vs 60.7%) and cyclosporine (11.8% vs 74.7%), and more frequently used tacrolimus (91% vs. 27,3%). In the outcomes, graft loss had no difference between periods; however, decompensation was more frequent (p=0.007) and patient’s survival was lower in the more recent period (p=0.032). NC (n=201) and C (n=23) were compared. C patients were older (49 vs 41.6 y), with more males(87% vs 65%), greater number of previous RTx (48% vs 18%), lower use azathioprine (26% vs 54%), less use of cyclosporine (13% vs 46.5%), more use of tacrolimus (87% vs 55%), lower count of platelets x 1000 cells/mm3 (110 vs 187) and higher pré-RTx INR (1.20 vs 1.1).The Kaplan-Meier survival curves differed C vs NC only in hepatic decompensation. Cox regression analysis identified pre-transplant cirrhosis HR6.64, p<0.001 and the use of tacrolimus HR 3.17, p=0.041 as variables that were independently associated with decompensation. Conclusions: The profile of RTx with hepatitis C has changed over the last 20 years. Despite a decrease in the prevalence of HCV, new clinical challenges have emerged, such as a more advanced age and a higher prevalence of cirrhosis. Cirrhotic exhibit higher morbidity when submitted to RTx than non-cirrhotic, with a higher risk of hepatic decompensation. However, no difference was observed in liver-related mortality, suggesting that RTx is a feasible option in cirrhotics without decompensation, even if they have portal hypertension.